Electronic payment cards and their role in achieving the competitive strategy for the activation of financial technology – An analytical study of a sample of Algerian public bank customers - Boussouak, Amel; Hamlaoui, Sakina; Salah, Rahima Bousbia; Tuoahri, Sarra (The International tax journal, 2025)
This study addresses the significance of electronic payment cards as an endeavour to realise the competitive strategy for activating financial technology. It aims to raise awareness and highlight the importance of embracing information technology and digital transformation due to their impact on achieving financial savings. Through the analysis and examination of the questionnaire data, we identified the extent of the relationship between the use of electronic payment cards and the implementation of a competitive strategy for digital banking transformation. This was achieved by evaluating and analysing clients' perspectives from Algerian public bank branches using the statistical software SPSS22. The study concluded that there is a correlational relationship between the use of electronic payment cards and the implementation of a competitive strategy for digital transformation, as well as the increased activation of financial technology in Algerian banks.